KAJIAN NILAI EGALITARIAN DALAM KITAB PURANA SEBAGAI ACUAN DALAM KEHIDUPAN BERMASYARAKAT - Made Adi Nugraha Tristaningrat (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
The library is the most important Puranas which we know in the Hindu Puranas, because it is the first step to learn or understand Vedas. The Puranas are part of Vedic Smriti, which has an important and strategic position in the sequence of the Vedas and the Chedi. In Siva Purana, Siva is known as the Supreme God and many devotees. The myth of Siva can be found in some Hindu scriptures, namely books of Brahmins, Mahabharata, Puranas, and religion. In the oldest Hindu scriptures, the Vedas, although the name of Siva Samhita itself is never pecified, but it is actually the seeds of the embodiment of the character Siva itself has been in existence, namely the Rudra. In the course of the story Siva Purana, there are some conflicts means life for the sake of supporting life in the present. The meanings of these are expected to be examined until analyzed theoretically so that meaning can be applied are contained in this present life. There are many conflicts which gave rise to the meaning in some episodes in the Puranas, one piece of a conflict between the God Siva, Brahma, and the God Visnu. The conflict leads to equality in life known as the egalitarian. This concept is important for the life of the present to create harmoniousrelationships between each other.